PERAN CORPORATE GOVERNANCE SEBAGAI VARIABEL MEDIASI PADA HUBUNGAN ANTARA GROUP AFILIASI DAN ASSET QUALITY INDEX TERHADAP PROFIT PERFORMANCE - Sari, Maya; Defung, Felicity; Ulfah, Yana (Penerbit Lafadz Jaya, 2026)
This study aims to examine the role of Corporate Governance as a mediating variable in the relationship between Group Affiliation, Asset Quality Index, and Profit Performance in palm oil agribusiness sub-sector companies listed on the Indonesia Stock Exchange. The study applies an explanatory quantitative approach using secondary data from annual reports and financial statements for the 2020-2024 period. The sample was selected through purposive sampling and consisted of 20 companies with 100 firm-year observations. Profit Performance is measured by Return on Assets (ROA), Group Affiliation is measured using a dummy variable, Asset Quality Index is calculated from the proportion of non-current assets to total assets, and Corporate Governance is proxied by the proportion of independent commissioners. The results show that Group Affiliation and Asset Quality Index have positive and significant effects on Corporate Governance at the 10% level. Group Affiliation has a negative and significant effect on ROA, while Asset Quality Index and Corporate Governance do not significantly affect ROA. The Sobel test indicates that Corporate Governance does not mediate the effects of Group Affiliation or Asset Quality Index on Profit Performance. These findings demonstrate that group affiliation does not automatically improve profitability when agency costs, related-party transactions, coordination burdens, and asset inefficiency outweigh the benefits of group synergy.